Atrazine and estradiol effects on development of Acris blanchardi (Blanchard's cricket frog) exposed in outdoor enclosures. Issue 11 (25th August 2022) - Windle, Shauni; McMurry, Scott; Brain, Richard; Maul, Jonathan; Wolf, Jeffrey; Belden, Jason
Abstract: BACKGROUND: The herbicide atrazine has been proposed as a potential endocrine disrupting compound (EDC) for amphibians. Using atrazine concentrations below or at those typically found in surface waters (0.5, 5.0, 50 μg/L), we exposed Acris blanchardi (Blanchard's cricket frog) larvae throughout development until metamorphosis (i.e . Gosner stages 26–45). An additional 50 μg/L treatment (50 s μg/L) was utilized where supplemented algae was added to control for indirect atrazine effects from reduced food sources. In addition to atrazine, experimental groups also included a negative control and two positive controls, 17β‐estradiol (E2) at 2.3 and 25 μg/L. At 60 days post‐metamorphosis, A. blanchardi metamorphs were euthanized for analysis of gross and histopathological development. RESULTS: Atrazine did not significantly influence mortality (mean recovery of 54% across treatments), sex ratio, body mass (BM), snout‐vent length (SVL), gonad size, nor gonad development of A. blanchardi . Females exposed to 50 s μg/L atrazine had 29% less mass, were 10% shorter, and had a 29% lower mean ovary area (mm 2 ) as compared to negative controls, suggesting algae enrichment had a significant negative effect. Males exposed to estradiol (25 μg/L) showed an increased level of oviduct development. Ovary area was also significantly influenced by estradiol treatment at 2.3 and 25 μg/L. CONCLUSION: Overall, estradiol had much less effect than predicted based on other model species (e.g . Xenopus laevis ). Development of A. blanchardi, overall, was not affected by long‐term exposure to environmentally relevant concentrations of atrazine. However, this species also was largely insensitive to exogenous estradiol in this test system. © 2022 Society of Chemical Industry. Abstract : Acris blanchardi larvae were exposed to environmentally relevant concentrations of atrazine (0.5, 5, 50 μg/L) and 17β‐estradiol (E2) controls (2.3 and 25 μg/L) until metamorphosis. While development of A. blanchardi was not affected by atrazine exposure, histopathologic examination noted diminished ovary development and male oviduct development in E2 treated animals.